2017
DOI: 10.1371/journal.pone.0178973
|View full text |Cite
|
Sign up to set email alerts
|

Variability in CitXET expression and XET activity in Citrus cultivar Huangguogan seedlings with differed degrees of etiolation

Abstract: Considering the known effects of xyloglucan endotransglycosylase (XET) on plant growth and development, we aimed to determine whether XETs help to regulate the growth and elongation of Huangguogan shoots and roots. We confirmed a possible role for XET during seedling etiolation. Our results revealed that the roots of etiolated seedlings (H-E) were longer than those of green seedlings (H-G). However, shoot length exhibited the opposite pattern. We also observed positive and negative effects on the xyloglucan-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…There were eight optimal codons of CitXET (i.e., AGA, AUU, UCU, CUU, CCA, GCU, GUU, and AAA), suggesting CitXET was biased toward the synonymous codons with A or U at the third codon position. We found that XET activity was specific to the elongation of root cells during citrus seedling etiolation in previous research [ 42 ]. Consequently, the codon usage bias may be very closely related to the functionality of CitXET .…”
Section: Discussionmentioning
confidence: 89%
“…There were eight optimal codons of CitXET (i.e., AGA, AUU, UCU, CUU, CCA, GCU, GUU, and AAA), suggesting CitXET was biased toward the synonymous codons with A or U at the third codon position. We found that XET activity was specific to the elongation of root cells during citrus seedling etiolation in previous research [ 42 ]. Consequently, the codon usage bias may be very closely related to the functionality of CitXET .…”
Section: Discussionmentioning
confidence: 89%
“…All seedlings, used for the determination of photosynthetic characteristics, were collected and divided into shoots and roots. The root and shoot lengths were measured as previously described 44 . After the green removing process at 110 °C for 24 h, the dry weight of root and shoot was measured.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative real-time PCR (qRT-PCR) analysis using the Bio-Rad CFX Manager (Bio-Rad, USA) with SsoFastTM EvaGreen Supermix (Bio-Rad) was employed to verify the DEG expression results 23 . Primers (Table 2) for specific genes encoding photosynthesis DEGs were designed using Primer3 (http://bioinfo.ut.ee/primer3-0.4.0/) and synthesized by Sangon Biotech 44 . All primers were amplified with no template control to make sure the amplicons were not primer dimers.…”
Section: Methodsmentioning
confidence: 99%
“…Rootstock is an important part of the Citrus industry as it influences scion characteristics such as fruit quality, canopy size, and resistance 8,9 . Previous studies have demonstrated that Citrus -grafted seedlings with Pt as rootstock were prone to nutrient deficiency and growth retardation in calcareous soils 10,11 . However, Ziyang xiangcheng ( Citrus junos Sieb.…”
Section: Introductionmentioning
confidence: 99%